2020
DOI: 10.1038/s41431-020-0654-4
|View full text |Cite
|
Sign up to set email alerts
|

A second cohort of CHD3 patients expands the molecular mechanisms known to cause Snijders Blok-Campeau syndrome

Abstract: There has been one previous report of a cohort of patients with variants in Chromodomain Helicase DNA-binding 3 ( CHD3 ), now recognized as Snijders Blok-Campeau syndrome. However, with only three previously-reported patients with variants outside the ATPase/helicase domain, it was unclear if variants outside of this domain caused a clinically similar phenotype. We have analyzed 24 new patients with CHD3 variants, including nine outside the ATPase/helicase domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 14 publications
4
61
1
13
Order By: Relevance
“…In general, this novel SMARCA5 -associated syndrome reported here appears to result in a less severe phenotype when compared to other neurodevelopmental disorders due to pathogenic variants in ARID, SMARC , and CHD gene families, where almost all of the variants occur de novo and parent-child transmission is rarely documented ( 49, 55 ). We present here a three-generation pedigree (for individuals 4-6) segregating a deleterious missense variant.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In general, this novel SMARCA5 -associated syndrome reported here appears to result in a less severe phenotype when compared to other neurodevelopmental disorders due to pathogenic variants in ARID, SMARC , and CHD gene families, where almost all of the variants occur de novo and parent-child transmission is rarely documented ( 49, 55 ). We present here a three-generation pedigree (for individuals 4-6) segregating a deleterious missense variant.…”
Section: Discussionmentioning
confidence: 66%
“…We identified six missense variants, one splice-altering variant that lead to exon skipping and in-frame deletion, and one recurrent in-frame deletion in eleven individuals from nine unrelated families from around the world. The individuals in our study demonstrated a broad range of clinical features, as is not uncommon in neurodevelopmental disorders associated with pathogenic variants in aforementioned chromatin remodeling complexes (i.e., SWI/SNF, CHD, and ISWI) that vary from isolated autism to syndromic intellectual disability ( 5, 17, 48, 49 ). The most consistent clinical findings in our cohort are postnatal microcephaly and short stature observed in 10/12 individuals, and developmental delay in 8/10 individuals, although again, the severity of these delays varies widely from mild to severe (individual 7).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We identified seven missense variants, one splice-altering variant that led to exon skipping and in-frame deletion, and one recurrent in-frame deletion in 12 individuals from 10 unrelated families from around the world. The individuals in our study demonstrated a broad range of clinical features, as is not uncommon in neurodevelopmental disorders associated with pathogenic variants in aforementioned chromatin remodeling complexes (i.e., SWI/SNF, CHD, and ISWI) that vary from isolated autism to syndromic intellectual disability (5,17,49,50). The most consistent clinical findings in our cohort are postnatal microcephaly and short stature observed in 10 of 12 individuals as well as developmental delay in 8 of 10 individuals, although, again, the severity of these delays varies widely from mild to severe (individual 7).…”
Section: Discussionmentioning
confidence: 71%
“…2 ) [ 208 ]. Patients with CHD3 mutations are only very recently identified with Snijders Blok–Campeau syndrome, which is characterized by ID (with a wide range of severity), developmental delays, macrocephaly, impaired speech and language skills, and characteristic facial features [ 209 , 210 ].…”
Section: Epigenetic Modulation During Neurodevelopment and Diseasementioning
confidence: 99%